Retraction: Combustion and emissions characteristics of a compression ignition engine fueled with n-butanol blends (2015 IOP Conf. Ser.: Mater Sci Eng. 100 012048). Issue 1 (February 2019) - Yusri, I M; Mamat, R; Ali, O M; Aziz, A; Akasyah, M K; Kamarulzaman, M K; Ihsan, C K; Mahmadul, H M; Rosdi, S M
Abstract : This paper has been retracted by IOP Publishing as it does not meet the terms of the IOP Proceedings Licence.